Diel, seasonal, and inter-annual variation in carbon dioxide effluxes from lakes and reservoirs. (1st March 2023) - Golub, Malgorzata; Koupaei-Abyazani, Nikaan; Vesala, Timo; Mammarella, Ivan; Ojala, Anne; Bohrer, Gil; Weyhenmeyer, Gesa A; Blanken, Peter D; Eugster, Werner; Koebsch, Franziska; Chen, Jiquan; Czajkowski, Kevin; et al.
Abstract: Accounting for temporal changes in carbon dioxide (CO2 ) effluxes from freshwaters remains a challenge for global and regional carbon budgets. Here, we synthesize 171 site-months of flux measurements of CO2 based on the eddy covariance method from 13 lakes and reservoirs in the Northern Hemisphere, and quantify dynamics at multiple temporal scales. We found pronounced sub-annual variability in CO2 flux at all sites. By accounting for diel variation, only 11% of site-months were net daily sinks of CO2 . Annual CO2 emissions had an average of 25% (range 3%–58%) interannual variation. Similar to studies on streams, nighttime emissions regularly exceeded daytime emissions. Biophysical regulations of CO2 flux variability were delineated through mutual information analysis. Sample analysis of CO2 fluxes indicate the importance of continuous measurements. Better characterization of short- and long-term variability is necessary to understand and improve detection of temporal changes of CO2 fluxes in response to natural and anthropogenic drivers. Our results indicate that existing global lake carbon budgets relying primarily on daytime measurements yield underestimates of net emissions.